1993
DOI: 10.1088/0953-8984/5/18/020
|View full text |Cite
|
Sign up to set email alerts
|

Phase front shapes in the KD2PO4paraelectric-ferroelectric transition

Abstract: The competition between the elastic energy and the elecmlatic energy induces particular shapes of the phase front at the KDzPOa first-order Vansition. nte coexistence of ule two phases is reported for a paraele&ic-femelecvic m i t i o n : the relevant domain textllies and dielectric properlies are described. It is shown that the Lilt angle between the phase front and the (001) plane never exceeds 22" in our experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The experimental results demonstrate that the phase front shape is completely different when the ferroelectric region is polydomain with a dense texture than when it is a monodomain one: as previously observed when a strong dc electric field E z is applied (Bastie et al 1980, Bornarel 1991, the phase front between the ferroelectric monodomain region and the paraelectric one is in an a plane parallel to the c axis. What happens when a small dc applied electric field E z is applied?…”
Section: Pf and Fp Transitions With A Small DC E Z Fieldsupporting
confidence: 64%
See 1 more Smart Citation
“…The experimental results demonstrate that the phase front shape is completely different when the ferroelectric region is polydomain with a dense texture than when it is a monodomain one: as previously observed when a strong dc electric field E z is applied (Bastie et al 1980, Bornarel 1991, the phase front between the ferroelectric monodomain region and the paraelectric one is in an a plane parallel to the c axis. What happens when a small dc applied electric field E z is applied?…”
Section: Pf and Fp Transitions With A Small DC E Z Fieldsupporting
confidence: 64%
“…If the crystal undergoes phase transition in these conditions, the phase front is observed as parallel to the c ferroelectric axis. Therefore the interface between both regions is non-charged (Bastie et al 1980, Bornarel 1991). In the case of small E z values, a polydomain texture exists corresponding to smaller electrostatic energy.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been noticed that domains were not observable in the initial stage of the PF phase transition. 24,25 But those observations have been made on a crystal under an external thermal gradient G e equal to 0.2 K mm Ϫ1 . From the present experiment with a very small thermal gradient, G e equal to 5ϫ10 Ϫ3 K mm Ϫ1 , which corresponds roughly to G i equal to 2ϫ10 Ϫ3 K mm Ϫ1 inside the crystal, 26 it can be concluded that the ferroelectric phase occupies a considerable volume of the sample whereas there are still only a few domains.…”
Section: B Domain Structurementioning
confidence: 99%
“…Dielectric measure-ments and observations along the three tetragonal axes were simultaneously performed giving a good knowledge of the phase coexistence phenomena and of the phase front shape. [22][23][24] The great importance of an external thermal gradient G e has been demonstrated: for G e between 10 Ϫ1 and 10 Ϫ2 K mm Ϫ1 , the phase front shape and orientation change with G e orientation. When G e is parallel to the ferroelectric c axis the phase front is quasiplanar and near ͑001͒ plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation